Characterization of prenatal healthcare for implementation of congenital toxoplasmosis surveillance program: Cross-sectional study - Benitez, Aline Do Nascimento [UNESP]; Gomes, Jancarlo Ferreira [UNESP]; Dias, Milenne Ura Seixas Santos [UNESP]; Navarro, Italmar Teodorico [UNESP]; Mitsuka-Breganó, Regina [UNESP]; Bresciani, Katia Denise Saraiva [UNESP] (FapUNIFESP (SciELO), 2020)
BACKGROUND: Prenatal toxoplasmosis remains a neglected disease worldwide and few government programs focusing on its prevention are available. Success in these programs has been extensively reported in the literature, yet the strategies used for their implementation, as a model for such actions in different communities, have not been described. OBJECTIVES: To describe the aspects of prenatal care strategies in 13 municipalities within the regional healthcare unit of Araçatuba, in the northwestern region of the state of São Paulo in 2017, focusing on congenital toxoplasmosis. DESIGN AND SETTING: Descriptive study on prenatal healthcare within the Brazilian National Health Sys-tem, in 13 participating municipalities. METHODS: Data on serological tests, referral clinics, notifications, healthcare strategies, health education and drugs for infected children were requested through a questionnaire that was sent via e-mail to people responsible for healthcare services in these municipalities. RESULTS: Major differences relating to diagnoses, reference outpatient clinics, notifications, health education and healthcare and drugs for infected children were reported among the prenatal strategies of these 13 municipal healthcare services. CONCLUSIONS: The lack of standardized prenatal strategy in the study area may compromise the prevention of infection. However, our identification of each aspect of prenatal care corroborates the need to implement a healthcare surveillance program relating to congenital toxoplasmosis.
Keywords: AUTHORS’ Preventive measures; Gestation; Health policies; Pregnancy; Prevention and control [subheading]; Protozoan infections; Public health; Toxoplasma; Zoonoses